2010
DOI: 10.1089/ten.tec.2009.0492
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of Outgrowth Endothelial Cells in High and Low Colony-Forming Cultures from Peripheral Blood Progenitors

Abstract: An effective isolation protocol for outgrowth endothelial cells (OEC) resulting in higher cell numbers and a reduced expansion time would facilitate the therapeutical application. In this study a standard protocol based on the isolation of mononuclear cells from adult peripheral blood was modified by adding a passaging step 7 days after the isolation. OEC colonies gained by both protocols were evaluated after 28 days and resulted in different frequencies of OEC colonies depending on the donor and culture proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 35 publications
2
31
2
1
Order By: Relevance
“…Late EPCs could only be established from buffy coat, whereas early EPCs could be established from both WBC filters and buffy coat with the latter giving rise to a higher yield of early EPCs. We were unable to confirm the early reports from other groups that early EPCs (Teleron et al, 2005) and late EPCs (Ingram et al, 2004;Yoder et al, 2007;Estes et al, 2010;Kolbe et al, 2010) could be established from whole blood. This discrepancy may be caused by the difference in the source and status of the whole blood used.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Late EPCs could only be established from buffy coat, whereas early EPCs could be established from both WBC filters and buffy coat with the latter giving rise to a higher yield of early EPCs. We were unable to confirm the early reports from other groups that early EPCs (Teleron et al, 2005) and late EPCs (Ingram et al, 2004;Yoder et al, 2007;Estes et al, 2010;Kolbe et al, 2010) could be established from whole blood. This discrepancy may be caused by the difference in the source and status of the whole blood used.…”
Section: Discussioncontrasting
confidence: 94%
“…In addition, the number of EPC colonies established from buffy coat blood in this study was also lower than that reported in previous studies using fresh whole blood (Ingram et al, 2004;Yoder et al, 2007;Estes et al, 2010;Kolbe et al, 2010). The low recovery of EPCs may be because buffy coat blood used in this study was platelet depleted.…”
Section: Discussioncontrasting
confidence: 74%
“…OEC for these experiments were used in passages 9-13. OEC from the different passages were characterized before by flow cytometry and several other methods as already described in previous publications, 23,24 indicating a high purity of (95%) for endothelial markers such as CD31, CD146, and VE-cadherin and a high phenotypic stability during the expansion.…”
Section: Isolation and Expansion Of Oecmentioning
confidence: 99%
“…In addition, osteogenic differentiation is also stimulated simultaneously by SHH. 22,24 Nevertheless, SHH is a potent and multi-facetted molecule that also carries potential risks. The present study shows that a potentially safer stress treatment, namely MHS, can also up-regulate both VEGF and Ang-1 in pOB mono-cultures and in co-cultures of OECs and pOBs and thus offers an additional means to support prevascularization.…”
Section: Et Almentioning
confidence: 99%
“…The first step is the isolation of stem cells from a source. For the purpose of banking or clinical application, stem cells can be isolated from a variety of sources including umbilical cord (Can and Balci, 2011;Zhang et al, 2011), adipose tissuederived stem cells (Insausti et al, 2011;Zachar et al, 2011), peripheral blood stem cells (Kolbe et al, 2010;Hofmann et al, 2009), amniotic and placental stem cells (Klein and Fauza, 2011;Tsagias et al, 2011), dental pulp stem cells (Gronthos et al, 2011;Tirino et al, 2011), olfactory stem cells (Chen et al, 2006;Viktorov et al, 2008), and even human limbal epithelial stem cells (Vasania et al, 2011).…”
Section: Introductionmentioning
confidence: 99%